Disentangling the minimum wage puzzle : an analysis of job accessions and separations from a longitudinal matched employer- employee data set - Portugal, Pedro (2001)
Changes in the legislation in mid-80s in Portugal provide remarkable conditions for economic analysis, as the minimum wage increased very sharply for a very specific group of workers. Relying on a matched employer-employee panel dataset, we model gross job flows - accessions and separations - in continuing firms, as well as in new firms and those going out of business, using a Poisson regression model applied to proportions. Worker behaviour is as well modelled. Employment trends for teenagers, the affected group, are contrasted against older workers, before and after the rise in the youth minimum wage. The major effect on teenagers of a rising minimum wage is the reduction of separations from the employer, which compensates for the reduction of accessions (to new and continuing firms) and the rising dismissals from firms closing down. This result suggests the relevance of supply side factors overcoming demand forces, as they indicate that job attachment for low wage youngsters rises following an increase in their minimum wage. In this sense, our results can reconcile some of the previous evidence that has been presented in the empirical literature when analysing the overall impact of the minimum wage on youth employment without looking at its sources.